Electroacupuncture Pretreatment Alleviates Cerebral Ischemia-Reperfusion Injury by Increasing GSK-3β Phosphorylation Level via Adenosine A1 Receptor. (21st February 2020) - Geng, Wujun; Cai, Libin; Han, Kunyuan; Li, Ding; Mo, Yunchang; Dai, Qinxue; Tang, Hongli; Zhang, Minyuan; Akuetteh, Percy David Papa; Balelang, Meita Felicia; Wang, Junlu
Abstract : Objective . To observe the effect of adenosine A1 receptor in the hippocampus of mice on GSK-3 β phosphorylation level and elucidate the underlying mechanisms of electroacupuncture pretreatment by activating Α1 receptor mediating cerebral ischemia-reperfusion injury. Method . The model of middle cerebral artery occlusion (MCAO) was established and grouped into electroacupuncture pretreatment group (EA group), MCAO group, and sham-operated group (Sham group). The neurobehavioral manifestation, the volume of cerebral infarction, and its related protein changes in mice in each group were observed. Then, adenosine Α1 receptor antagonist and agonist were injected intraperitoneally to observe the effects of A1 receptor on the phosphorylation level of GSK-3 β, neurobehavioral changes, and infarction volume. Results . (1) Compared with the MCAO group (24 hours after reperfusion), the infarct size in the EA group decreased significantly, and the Garcia neurological score and phosphorylation level of GSK-3 β are increased. (2) Compared with the EA group, the infarct size in the A1 receptor antagonist 8-cyclopentyl-1, 3-dipropylxanthine (DPCPX) group increased significantly, and the Garcia neurological score and phosphorylation level of GSK-3 β are decreased. (3) Compared with the MCAO group, the infarct size in the A1 receptor agonist 2-Chloro-N6-cyclopentyladenosine (CCPA) group decreased significantly, and the Garcia neurological score and phosphorylation level of GSK-3 β are increased. There was no significant difference between the EA group and CCPA group. Conclusions . Electroacupuncture pretreatment can increase GSK-3 β phosphorylation level via activating A1 receptor, to protect neurons in ischemia-reperfusion injury.